Functional characteristics of an α-L-arabinofuranosidase secreted by the basidiomycete Coriolopsis byrsina - de Oliveira Nascimento, Carlos Eduardo [UNESP]; de Menezes, Cíntia Lionela Ambrosio [UNESP]; Boscolo, Maurício [UNESP]; da Silva, Roberto [UNESP]; Gomes, Eleni [UNESP]; da Silva, Ronivaldo Rodrigues [UNESP] (Springer Nature, 2023)
α-L-arabinofuranosidases can be produced by fungi, bacteria, and plants and are responsible for the cleavage of α-1,2, α-1,3, and α-1,5 glycosidic bonds in arabinose residues. Few recent studies have focused on the production of these enzymes by species of basidiomycetes. In the present study, we purified an α-L-arabinofuranosidase from the fungus Coriolopsis byrsina and evaluated its functional biochemical properties. The purified enzyme had an estimated molecular mass of 55 kDa with maximum activity at pH 3.5–4.5 and 50 °C, stability in the range of pH 3–8 at 4 °C for 24 h, and from 10 to 60 °C for 1 h. The enzyme was also stable in 5–10% ethanol after 24 h at 28 °C, retaining more than 60% activity. A negative effect on catalysis was noted for all evaluated ions, especially Fe3+ and Hg2+, retaining 25% and 33% activity, respectively, at 10 mmol L−1, and L-arabinose, with 50% activity at 0.2 mol L−1 and 30% at 0.9 mol L−1. The enzyme was active on p-nitrophenyl-α-L-arabinofuranoside (pNPA), p-nitrophenyl-β-D-xylopyranoside, linear 1,5 α-L-arabinan and xylan from beechwood. Kinetic assays under pNPA substrate indicated a KM of 3.45 ± 0.9 mmol L−1 and Vmax of 198.2 ± 24 μmol min−1 mg−1. These findings can serve as a reference for further tests of this enzyme aimed at improving the aroma of beverages and formulating enzyme cocktails for plant biomass degradation.
Keywords: Arabinan; Ethanol; Glycosidase; pNPA; Solid-state fermentation